Pengembangan Sektor Pariwisata Sebagai Upaya Meningkatkan Pendapatan Asli Daerah (Studi Kasus Pada Sektor Pariwisata Kabupaten Kediri) - Rifqi Zuchal Ghozali; Abu Talkah; Eka Askafi (Universitas Islam Kadiri, 2021)
Abstract The tourism sector is one sector that is utilized by various regions in Indonesia in increasing the independence and prosperity of its people. especially in the current era of regional autonomy, the Regional Government of Kediri Regency needs to develop the tourism sector as an effort to increase Local Revenue (PAD). The purpose of this study was to determine and analyze the condition of tourism in the District of Kediri, the development of the tourism sector, the factors that influence tourism development, as well as the obstacles experienced in developing tourism as an effort to increase the Regional Original Revenue (PAD) of Kediri Regency. The instrument in this study used interview guidelines conducted by direct observation of the research subjects. Based on the results of research and discussion that the condition of tourism in the area of ​​Kediri Regency has enormous potential as one of the supporting sectors of regional development. Tourism development has a large enough potential to continue to be increased so that it contributes to the increase in input on the Regional Original Revenue (PAD). Factors that influence the development of the tourism sector include established regulations, qualified and competent human resources, budget funds, and real participation from the community. Obstacles related to the development of the tourism sector are the low quality of Human Resources (HR) as a manager of tourism and tourism objects, the limited facilities and infrastructure as well as the marketing network, and the non-optimal management and development of the tourism potential of Kediri Regency. Keywords: Development, Tourism Sector, PAD, Kediri Regency.